Body mass index and attention bias of food cues in women: a mediation model of body weight dissatisfaction - Aibao Zhou; Pei Xie; Md Zahir Ahmed; Mary C. Jobe; Oli Ahmed (PeerJ, 2022)
Food attention bias could be used to indicate diet-related diseases in individuals with obesity. The purpose of this study is to explore the relationship between body mass index (BMI) and food attention bias, and the mediating role of body weight dissatisfaction (BWD) on this relationship in women. Seventy-five participants were recruited to complete a visual dot task with eye tracking. The results showed that BMI would positively predict response latency and duration bias on high-calorie foods; the relationship between BMI and response latency of high-calorie food was a complete mediation of BWD; the relationship between BMI and duration bias of high-calorie food was a complete mediation of BWD; and BWD positively predicts response latency and duration bias on high-calorie foods. These findings suggest a positive relationship between BMI and food attention bias, and the effect of a complete mediation of BWD in women.